Violence Against American Indian and Alaska Native Women and Men: 2010 Findings from the National Intimate Partner and Sexual Violence Survey (NISVS) - Rosay, Andre B. ([Verlag nicht ermittelbar], 2016)
This study examines the prevalence of violence against American Indian and Alaska Native women and men, using a large nationally representative sample from the National Intimate Partner and Sexual Violence Survey (NISVS). More specifically, it provides estimates of sexual violence, physical violence by intimate partners, stalking, and psychological aggression by intimate partners. It also provides estimates of interracial and intraracial victimizations and briefly examines the impact of violence. This study is based on two of the NISVS samples that were included in the 2010 data collection effort --the general population sample and the American Indian and Alaska Native oversample. This American Indian and Alaska Native oversample was collected from geographical areas (telephone exchanges) where at least 50% of the population identifies themselves as American Indian or Alaska Native. To increase the generalizability of the American Indian and Alaska Native sample (and to add interviews conducted by cell phone), a new "combined" sample was created by including (a) all respondents in the American Indian and Alaska Native oversample and (b) 677 respondents in the general population sample who identified themselves as American Indian or Alaska Native. By combining these samples, a new sample was obtained that is large enough to produce reliable and valid estimates for all women and men in the United States who identify themselves as American Indian or Alaska Native. For a more exact discussion of the sample, see the NIJ Technical Report. The combined sample includes 2,473 women and 1,505 men who identified themselves as American Indian or Alaska Native. Results from the combined American Indian and Alaska Native sample were compared to results from the sample of respondents in the general population sample who identified themselves as non-Hispanic White alone. The comparison sample includes 7,646 women and 6,050 men who identified themselves as non-Hispanic White alone. There are 5 data files included with this study. Dataset 1 (General Population Raw Data) contains 18,957 cases and 26,114 variables. Dataset 2 (American Indian and Alaska Native (AIAN) Oversample Raw Data) contains 3,612 cases and 22,932 variables. Dataset 3 (Respondent-level Data) contains 21,378 cases and 493 variables. Dataset 4 (Perpetrator-level Data) contains 51,535 cases and 446 variables. Dataset 5 (Weights File) contains 3,978 cases and 9 variables.